Targeted Raman Imaging of Cells Using Graphene Oxide-Based Hybrids - Zhang, Zhenyu (Langmuir : the ACS journal of surfaces and colloids, 2016)
Graphene oxide (GO) is a reliable and multifunctional platform to perform cell imaging. In this work, a controllable Pt-seed-mediated method is used to prepare GO/gold nanoparticle (AuNP) hybrids, and after the covalent binding of folic acid (FA), GO/AuNP/FA hybrids are prepared. Selective labeling and Raman imaging of folate receptor (FR)-positive HeLa cells are realized using such GO-based hybrids. In this system, FA is the targeting agent, AuNPs work as surface-enhanced Raman scattering substrates, and GO takes the role of both supporting the AuNPs with FA and acting as a Raman probe. This research further extends the application of GO as a multifunctional platform in bioimaging and other biomedical processes